Meta-analysis for public management and policy - Ringquist, Evan J. 1962-; Anderson, Mary R. (San Francisco, CA Jossey-Bass, 2013)
Praise for Meta-Analysis for Public Management and Policy "In his usual rigorous but readable style, Evan Ringquist and co-author Mary Anderson have produced a tour-de-force on the topic of meta-analysis in public policy and management research.
Includes bibliographical references (p. 514-542) and indexes.
Keywords: Public administration -- Statistical methods; Social sciences -- Statistical methods; Meta-analysis.